Perspective of the Pancasila on Religious Moderation (Analysis of Religious Development Communication) - Denny Al Anshori Daulay; M. Yoserizal Saragih (LEGAL BRIEF, 2022)
Indonesia is a country where you will be diverse in ethnicity and culture, indirectly Indonesia has become a pluralistic country. The thing that is currently a problem and is often discussed by the goverment and figures as well as elements of society in it is religious moderation. How to maintain, maintain and involve the whole community totolerate being wrapped in religious moderation (religious develovement communication) can be a solution to differences and sexual disputes, which are questions that will be discussed in this study.